2017
DOI: 10.1163/18759866-08604003
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected twist: Sperm cells coil to the right in land snails and to the left in song birds

Abstract: In animals, cell polarity may initiate symmetry breaking very early in development, ultimately leading to whole-body asymmetry. Helical sperm cells, which occur in a variety of animal clades, are one class of cells that show clearly visible bilateral asymmetry. We used scanning-electron microscopy to study coiling direction in helical sperm cells in two groups of animals that have figured prominently in the sperm morphology literature, namely land snails, Stylommatophora (514 spermatozoa, from 27 individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In the usual perception, sperms are thought to use the soft tail for swimming by rotating or beating (7)(8)(9), and the head is only a container of the genetic material. Some sperms of various species, such as cartilaginous fish (10)(11)(12), passerine birds (13)(14)(15)(16), some amphibians (17)(18)(19)(20), cephalodasys maximus (21), annelida (22), arthropoda (23), monotreme, and epiphanes senta, as reviewed by researchers (24,25), have a distinctive spiral head. Apart from the morphology studies, some researchers also reported the spinning motion of sperms with spiral head (26)(27)(28)(29), including their motility in viscous environments (30)(31)(32).…”
mentioning
confidence: 99%
“…In the usual perception, sperms are thought to use the soft tail for swimming by rotating or beating (7)(8)(9), and the head is only a container of the genetic material. Some sperms of various species, such as cartilaginous fish (10)(11)(12), passerine birds (13)(14)(15)(16), some amphibians (17)(18)(19)(20), cephalodasys maximus (21), annelida (22), arthropoda (23), monotreme, and epiphanes senta, as reviewed by researchers (24,25), have a distinctive spiral head. Apart from the morphology studies, some researchers also reported the spinning motion of sperms with spiral head (26)(27)(28)(29), including their motility in viscous environments (30)(31)(32).…”
mentioning
confidence: 99%
“…In songbirds, the acrosome has a helical membrane (also known as a helical keel) that spirals around the cell core, and recent evidence suggests that the direction of this helical spiral is sinistral (counterclockwise; Schilthuizen et al. ). Together, the helical core and helical membrane give songbird sperm a distinct spiral or corkscrew shape, and there appears to be substantial variation in this shape across species (Jamieson ).…”
mentioning
confidence: 99%
“…The acrosome is at the anterior of the head and contains enzymes that allow the sperm to penetrate the perivitelline layer of the ovum (Nishio and Matsuda 2017), while the nucleus contains the densely compacted DNA. In songbirds, the acrosome has a helical membrane (also known as a helical keel) that spirals around the cell core, and recent evidence suggests that the direction of this helical spiral is sinistral (counterclockwise; Schilthuizen et al 2017). Together, the helical core and helical membrane give songbird sperm a distinct spiral or corkscrew shape, and there appears to be substantial variation in this shape across species (Jamieson 2007a).…”
mentioning
confidence: 99%
“…But, curiously, they differ in the direction in which the head is twisted. Rotation of the sperm head in birds is clockwise whereas in land snails it is counter-clockwise (367). It is not clear how or why these sperm head forms have evolved and why there are so conserved within taxa.…”
Section: Birdsmentioning
confidence: 99%
“…Interestingly, a spirally twisted sperm head, as seen in passerine birds, is also seen in other taxa, such as land snails, but, curiously, they differ in the direction in which the head is twisted. Rotation of the sperm head in birds is clockwise, whereas in land snails it is counterclockwise ( 61 ). It is not clear how or why these sperm head forms have evolved and why they are so conserved within taxa.…”
Section: Sperm Structure and Functionmentioning
confidence: 99%